Accountancy as a career choice: The effect of influences on the intention to pursue professional accounting qualifications among current junior and senior BSA students in DLSU as mediated by interest in accounting - Chua, Jill Geraldyn L. (Animo Repository, 2023)
Just like any other career, choosing accountancy as a career is a dynamic and critical process determining one’s future and quality of life. Observing the integration of the Theory of Planned Behavior (TPB) and the Social Cognitive Career Theory (SCCT), this study aimed to investigate the impact of the influences (i.e., attitude toward accounting, subjective norms, perceived behavioral control, outcome expectations, and interest in accounting) on the intention to pursue professional accounting qualifications (i.e., CPALE or other accounting certifications) with interest as the mediator and culture, age, and gender as moderators. The study adopted a cross-sectional, explanatory, and confirmatory design which collected data from 240 junior and senior accounting students through a quantitative survey conducted both online and in person. Results obtained from the PLS-SEM analysis emphasized that only the attitude, outcome expectations, and interest were relevant on such intention, in which interest provided a full mediation on the effect of perceived behavioral control on intention. Culture, age, and gender were all found to moderate the interest-intention relationship. Besides interest-intention, culture moderated the relationship that perceived behavioral control and outcome expectations has on intention, while gender moderated the relationship shared by outcome expectations with intention. With these results, recommendations for accounting students, professionals, and management regarding the interplay of TPB and SCCT’s intention hypotheses were discussed to better understand and facilitate the process of choosing a career in accounting. Key Words: behavioral intention; professional accounting qualifications; interest in accounting; career choice